Implementation Of Extracurricular Dance Art In Stimulating Children's Gross Motor Skills In The Muslim Cadani Integrated Islamic Kindergarten In The 2024/2025 Academic Year - Hotimah, Nurul; Arzani, M.; Ramzi, Muhajirin (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to determine the implementation of dance in the Islamic at TK of Mulsim Madani Integration and to describe the role of teachers in supporting the success of extracurricular dance activities in children. In addition, this study aims to analyze the characteristics of dance movements that are most effective in encouraging children's gross motor development at the Madani Muslim Integration Islamic Kindergarten in the 2024/2025 academic year.This type of research is qualitative research with a case study approach, the data collection techniques used in this research are observation, interviews, and documentation. The information collected came from the person in charge of extracurricular dance and the principal. With the research model from Milles and Hubberman. The data analysis technique used in this research is through several stages including 1) Data condensation. 2) Data Display, and 3) Drawing Conclusions.The results of this study reveal that dance extracurricular activities at Madani Muslim Integration Islamic Kindergarten are carried out once a week (Friday, at 10.00) With participants free to choose extracurricular activities according to their preferences. The teaching methods include visual (imitating the spectacle) and visual (imitating the spectacle). Teaching methods include visual (imitating the spectacle), repetition (repetitive movements), and motion exploration (monitored freedom). The teacher serves as a motivator (providing support and rewards) and facilitator (preparing facilities, comfortable environment). Dance movements are designed according to children's gross motor abilities, with modifications. Dance movements are designed according to children's gross motor abilities, with modifications to facilitate learning. Some of the effective movements taught include dynamic movements, pattern variations, nature/animal imitation, and social interaction, which significantly promote children's gross motor development.